The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/children9060865
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Radiographs and the Pirani Score for Later Additional Surgery in Ponseti-Treated Idiopathic Clubfeet, an Observational Cohort Study

Abstract: There are few validated predictors of the need for additional surgery in idiopathic clubfeet treated according to the Ponseti method. Our aim was to examine if physical examination (Pirani score) and radiographs at the age of three months (after initial correction of the clubfeet) can predict the future need for additional surgery. In this retrospective cohort study, radiographs of idiopathic clubfeet were made at the age of three months. The Pirani score was determined at the first cast, before tenotomy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We found that a cutoff point of > 70 degrees could predict fair-to-poor functional outcome at walking age with 88.9% sensitivity, similar to the equinus position, which results in a poor quality of life. Similarly, previous studies recommended using this angle to predict risk of relapse and decide the surgical type, such as Achilles tenotomy, soft tissue release, and even reconstructive procedures for recurrent clubfoot, to improve functional outcome, but these studies investigated older children[ 8 , 10 , 11 , 22 , 23 ]. Additionally, a close relationship of clinical and talocalcaneal and talo-1 st metatarsal angles was found in some studies[ 17 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that a cutoff point of > 70 degrees could predict fair-to-poor functional outcome at walking age with 88.9% sensitivity, similar to the equinus position, which results in a poor quality of life. Similarly, previous studies recommended using this angle to predict risk of relapse and decide the surgical type, such as Achilles tenotomy, soft tissue release, and even reconstructive procedures for recurrent clubfoot, to improve functional outcome, but these studies investigated older children[ 8 , 10 , 11 , 22 , 23 ]. Additionally, a close relationship of clinical and talocalcaneal and talo-1 st metatarsal angles was found in some studies[ 17 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%